Biological characteristics and classification of the thermophilic bacteria BML07 strain producing both thermostable amylase and cellulase isolated from my lam hot spring - Dinh Man, Tran; Kim Thoa, Nguyen; Thi Da, Nguyen; Quoc Viet, Nguyen (Vietnam Journal of Science and Technology, 2017)
The thermophilic bacteria strain BML07 was  isolated from sedimental sludge of My Lam hot  spring  (Tuyen  Quang  province,  Vietnam).  Furthermore,  this  strain  became  promising candidate due to its capable of producing thermostable enzymes such as cellulase and amylase. The biophysiological characteristics of  this strain revealed  the optimal conditions for growth at pH  7.5;  2  -  3% NaCl,  and  70 oC,  however  it  is  still  able  to  survive  at  80 oC. Observation  of colony resulted in round shape and white, its cells obtained rod-shape (0.4 - 0.6 µm × 1.3 - 1.5 µm), positive Gram. Therefore, this strain was classified continuously based on Kit API 50/CHB as well as sequence of 16S rRNA. According to the taxonomical results using APIWEB software, the strain BML07 is similar of 97 % as Geobacillus caldoxylosilyticus (AY608950), however the sequence  of  1500  bp  fragment  coding  for  16S  rRNA  indicated  that  the homologous  sequence between this strain and Geobacillus caldoxylosilyticus (AY608950) strain raised up to 99.8 %, as hence its own named Geobacillus caldoxylosilyticus BML07.